Evaluation of lung capacity as a function of current volume in university students during the COVID-19 pandemic - Espinoza Quispe, Solange Marcelina (2021)
Objective. To evaluate lung capacity as a function of current volume (CV) and to analyze its influence in the presence of various external factors, such as physical activity (swimming), feeding and respiratory infection. Methods.The study was observational, descriptive, transversal and prospective. An online survey was conducted on a random sample of 50 university students between the ages of 17 and 20. CV was measured using a home spirometer and was classified under the IBM SPSS Statistics-24 program for statistical analysis. Results. From the surveys, the following data was obtained: the average CV of swimming students was (797.0 ± 2.0) ml. The average CV of students following a healthy diet was (567.00 ± 2.0) ml and the average CV of those with a respiratory history was (429.0 ± 2.0) ml. Conclusions. Having a diet rich in fruits and vegetables or having some physical activity greatly increases the lung capacity of the individual.